1968
DOI: 10.1002/ar.1091600413
|View full text |Cite
|
Sign up to set email alerts
|

The role of Spleen in development of lympho‐hemopoietic tissues: Effect of splenectomy on development of blood cells, bone marrow, thymus and lymph node

Abstract: The effects of splenectomy at birth and two and four weeks of age on the development of lymphoid and hematopoietic tissues has been compared in C3H/Bi mice. During the neonatal period normal mice showed changes in total leukocyte count, and in absolute members of the specific cell types. The predominant changes included an initial fall of numbers of granulocytes and steady increase in numbers of lymphocytes during the first six weeks of life. Neonatal splenectomy interfered with the normal developmental patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In our other previous studies [3,7,8], we have shown that splenecto my early in life leads to a shift of population from predominantly small thymocytes to thymocytes of medium size in the thymus. This interesting influence is coupled with a change in the cellular composition of the bone marrow and a decrease of circulating small lymphocytes in the peripheral blood.…”
Section: Discussionmentioning
confidence: 70%
“…In our other previous studies [3,7,8], we have shown that splenecto my early in life leads to a shift of population from predominantly small thymocytes to thymocytes of medium size in the thymus. This interesting influence is coupled with a change in the cellular composition of the bone marrow and a decrease of circulating small lymphocytes in the peripheral blood.…”
Section: Discussionmentioning
confidence: 70%